Імітаційне моделювання теплообмінника для підігрівання виноградного соку як об’єкта керування - Мірошник, В. О.; Лендєл, Т. І. (Енергетика і автоматика, 2017)
SIMULATION OF THE HEAT EXCHANGER FOR HEATING WINE AS A CONTROL OBJECT V. Miroshnyk, T. Lendiel The mathematical description of the object of study allows for the purposes of simulation modeling to design control systems, analysis and evaluation of the operation of the object. Since heat exchangers are complex objects, which is important convective process that is the combined action of heat conduction and convection. According to the design of the facility originally created simulation model, which is then investigated. To develop a simulation model heat exchanger wine for investigation of channel temperature adjustment to reflect changes the characteristics of the juice and the heating steam. Today in the processing industry for heating liquids or mixtures of superheated steam are widely used shell and tube heat exchangers. These heat exchangers are odnohodovymy or multi. Heat transfer in the heat exchanger takes place in two stages: from the hot coolant to the tubes through which coolant is cold and from them to the product (cold coolant) . In static mode it can be described as a balance of heat flow in pipes and heat exchanger fluid. The influence of expenses on juice and juice the final temperature time constant object on channel temperature control. Costs juice changed from 6 to 10 t / h and this changes the coefficient of heat transfer from tubes to the juice, which is due to the fact that the temperature of the juice to increase output, and changes the time constant of the object. Conclusions Developed simulation model of the heat exchanger to heat the grape juice. The influence of the final cost of juice and juice temperature time constant object on channel temperature control. It was determined that when the cost of juice from 6 to 10 t / h heat transfer coefficient varies from tube to juice costs themselves, which as a result of temperature increases the output of juice.